Cleft Habitus in the Health Promotion Learning During Covid-19 Pandemic (A Case Study of Students of Megarezky University) - Hairuddin K.; Andi Meinar Dwi Rantisari; Hasnawati S (STAI Hubbulwathan Duri, 2022)
The aims of this study were to describe the learning strategies of lecturers and students, to analyze Cleft Habitus in the learning process of health promotion for lecturers and students, to interpret the implications of Cleft Habitus in health promotion learning due to the Covid-19 pandemic. The research method used descriptive qualitative with data collection stages including purposive sampling and snowball sampling, non-participatory observation, in-depth interviews and documentation. The results of the study show that lecturer strategies in learning process were very diverse. New forms of habitus in the learning process of health promotion formed by lecturers and students were very diverse starting from the habitus of learning methods, the habitus of learning models or learning approaches, the habitus of learning evaluation, and the habitus of health protocols. It can be concluded that Covid-19 pandemic has led to Cleft Habitus in the learning process, including learning about health promotion for lecturers and students of the nursing study program of Megarezky University.